Implementation of A Graded Point System As An Alternative in Increasing Learning Interest in Sociology Study - Rahmi Hidayat; Syaharuddin Syaharuddin; Mutiani Mutiani (STKIP Taman Siswa Bima, 2024)
The low of student motivation and interest in learning during the COVID-19 pandemic continued to occur even when PTM (face-to-face learning) was held. This research aims to determine the effectiveness of implementing a graded point system as an alternative to increasing learning interest in sociology. This research uses a descriptive-qualitative method with a naturalistic approach. Data was obtained through observation, interviews, and documentation. The population in this research was 150 class XI students at SMAN 5 Banjarmasin. The subjects in this research were 75 students. Data analysis was carried out using narrative and discourse analysis. Based on the research results, it was found that the application of a graded points system can encourage more active interaction between students and teachers. Students also show higher enthusiasm for learning with the implementation of a graded points system in learning. Thus, it can be concluded that the application of the graded point system is quite effective as an alternative for increasing students' interest in learning.